Plea bargaining as a solution for criminal case backlog in Indonesia - Hakim, Lukman; Zulhuda, Sonny (Hampstead Psychological Associates, 2020)
Criminal Justice System in Indonesia has not been able to overcome criminal case backlog in courts. Besides the report from the Supreme Court about the large backlog of criminal cases in judicial institution, there was also a research which showed that judges in Indonesia tend to arrive at guilty verdicts on criminal acts with minor criminal charges (sanction under 5 years). The concept of Plea Bargaining which has been known and applied in several countries will also be included in Article 198 paragraph (5) and 199 of the Draft of Criminal Procedure Code (RKUHAP) in Indonesia which will be made as law. Although non-explicit verb is named as Plea Bargaining, the spirit of these articles are similar to the plea bargaining system which has been practiced in many countries and is considered successful in overcoming the criminal case backlog in courts, therefore the study uses comparative study of plea bargaining system in several countries and also uses normative research method and carried out by using the statutory approach through a review of laws and regulations as well as regulations relating to the issue discussed. Legal materials are obtained from the Criminal Procedure Code (KUHAP) and the Draft of Criminal Procedure Code (RKUHAP) which has been in the final discussion at the House of Representatives and Government, and in addition, the secondary legal materials are obtained from books, journals and other literature. Meanwhile, the data collection technique used is a library research by examining legal materials relevant to the research discussion.